2018
DOI: 10.1094/mpmi-01-17-0015-r
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of TvCyt2, a Member of the p450 Monooxygenases From Trichoderma virens Relevant During the Association With Plants and Mycoparasitism

Abstract: Secondary metabolites are crucial for the establishment of interactions between plants and microbes, as in the case of Trichoderma-plant interactions. In the biosynthetic pathway of secondary metabolites, specific enzymes participate in the formation of hydroxyl and epoxy groups, belonging to the p450 monooxygenases family. Here, we show that the product of the gene TvCyt2 from Trichoderma virens encodes a new protein homologous to the cytochrome p450, which is down-regulated at the beginning of Trichoderma-Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Recently, a T. virens P450 (TvCyt2; Protein Id. 190045) has been shown to be involved in biocontrol and plant growth promotion [ 46 ]. Basidiomycetes are capable of metabolizing a wide range of endogenous and exogenous compounds by using cytochrome P450s [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a T. virens P450 (TvCyt2; Protein Id. 190045) has been shown to be involved in biocontrol and plant growth promotion [ 46 ]. Basidiomycetes are capable of metabolizing a wide range of endogenous and exogenous compounds by using cytochrome P450s [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…are prolific producers of secondary metabolites, many with antimicrobial, anticancer and plant growth-promoting properties [ 45 ] Cyps are known to play central role in biosynthesis if many, if not most of the secondary metabolites of plant and microbial origin. Till date, however, only a handful of Trichoderma Cyps have been investigated for their role in biosynthesis of secondary metabolites [ 46 , 66 , 67 ]. Our present findings suggest that more than 20% of the catalogued Cyps from Trichoderma are part of putative secondary metabolism-related gene clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The expression pattern of some of these genes was analyzed during the Trichoderma–Arabidopsis interaction, observing the upregulation of genes grouped in LysM proteins, Serine-proteases, Thioredoxins, Hydrophobins, CFEM, and Cerato-platanin families. Down-regulation was also observed, as in the case of the Tvmp1 gene, encoding for a Metalloprotease (Guzmán-Guzmán et al, 2017), and for the Tvcyt2 gene, which encodes a p450-cytochrome (Ramírez-Valdespino et al, 2018). However, more than 200 sequences from this in silico analysis were not studied further and their possible function during Trichoderma –plants interaction remains unknown.…”
Section: Proteins As Effectors In Trichoderma–plant Interactionsmentioning
confidence: 99%
“…The enzyme encoded by the G3 gene in Trichoderma hamatum is activated in response to Sclerotinia and Sclerotium species (Carpenter et al, 2008). Through the generation of mutant and overexpressing strains of the Tvcyt2 gene of T. virens , five terpene-like compounds were identified as involved in the antagonistic activity against Rhizoctonia solani , in the activation of genes related to the JA pathway in Arabidopsis plants as well as in the promotion of growth in Arabidopsis and tomato seedlings (Ramírez-Valdespino et al, 2018).…”
Section: Secondary Metabolites As Effectors In Trichoderma–plant Intementioning
confidence: 99%
“…During mycoparasitism, a host fungus is parasitized by and provides a nutrient source for another biocontrol fungus, such as species of the genus Trichoderma , and C. rosea ( Karlsson et al, 2017 ; Nygren et al, 2018 ). Mycoparasitism comprises several steps; when encountering a fungal host, mycoparasites trigger gene expression associated with recognition, penetration, and parasitism, through various mechanisms related to mycoparasitism, antifungal activity, competition, and production of cell wall-degrading enzymes ( Qualhato et al, 2013 ; Lysoe et al, 2017 ; Gomez-Rodriguez et al, 2018 ; Ramirez-Valdespino et al, 2018 ). Our findings confirmed that the deletion of CrSsd1 severely impaired C. rosea antagonistic activity and mycoparasitic ability to S. sclerotiorum and B. cinerea and dramatically decreased the control efficacy against soybean Sclerotinia rot.…”
Section: Discussionmentioning
confidence: 99%